2022
DOI: 10.1007/s00066-022-01925-2
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy in oligometastatic prostate cancer—a pattern of care survey among members of the German Society for Radiation Oncology (DEGRO)

Abstract: Purpose Due to improved imaging, oligometastatic prostate cancer (OMPC) is diagnosed more frequently. Growing evidence shows that patients with a limited number of metastases benefit from primary-directed radiotherapy (PDT) as well as from metastasis-directed radiotherapy (MDT). This survey investigates the current treatment practice for OMPC among German-speaking radiation oncologists. Methods Members of the German Society for Radiation Oncology (Deutsche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…In other studies, there was a lack of prospective data regarding the influence of these factors on outcomes in patients with oligometastatic prostate cancer. Owing to multiple studies of prostate cancer and other diseases, there has been a drive for use of MDT for prostate cancer based primarily on the number of metastatic sites, as noted by expert consensus opinions, surveys, and national guidelines . Our inclusion criteria were designed for generalizability to reflect the clinical setting in which patients present to clinics predominantly based on the number of metastases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other studies, there was a lack of prospective data regarding the influence of these factors on outcomes in patients with oligometastatic prostate cancer. Owing to multiple studies of prostate cancer and other diseases, there has been a drive for use of MDT for prostate cancer based primarily on the number of metastatic sites, as noted by expert consensus opinions, surveys, and national guidelines . Our inclusion criteria were designed for generalizability to reflect the clinical setting in which patients present to clinics predominantly based on the number of metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to multiple studies of prostate cancer and other diseases, 17,35,36 there has been a drive for use of MDT for prostate cancer based primarily on the number of metastatic sites, as noted by expert consensus opinions, surveys, and national guidelines. 6,7,16,37,38 Our inclusion criteria were designed for generalizability to reflect the clinical setting in which patients present to clinics predominantly based on the number of metastases. Ultimately, the findings from this study are consistent with those of prior studies [8][9][10] in highlighting the benefit of MDT in a more generalizable clinical population and in combination with hormone therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of existing knowledge gaps, MDT has gained widespread acceptance as a treatment option across various settings of omPCa, including common use beyond clinical trials to bolster treatment in conjunction with systemic and/or interventional therapies. A recent survey conducted by the DEGRO group revealed that almost all radiation oncology respondents favored MDT for oligometastatic recurrence in PCa patients, with over half considering combining MDT with systemic therapy [ 4 ]. Notably, more than half of those surveyed did not differentiate between synchronous and metachronous disease, even though the evidence for MDT in PCa primarily stems from metachronous omPCa [ 3 ▪ ].…”
Section: General Overview Of Metastasis-directed Therapy In Context O...mentioning
confidence: 99%
“…Considering our evolving knowledge of tumor biology, the continuous interplay between different subclones and disease sites, introduction of anticancer therapies, and relying on aggravating the host response, utilizing strict imaging-based thresholds for the maximum number of metastases or organs involved may lead to an arbitrary classification, resulting in suboptimal treatment selection and oncologic outcomes. This issue is reflected by the results of a survey among the Members of the German Society for Radiation Oncology (DEGRO) and the omBC consensus [11 ▪▪ ,32 ▪ ]. According to 25.7% of DEGRO survey responders, the maximum number of lesions should be determined based on the ability to deliver curative treatment to the metastases [32 ▪ ].…”
Section: Conclusion and Future Challengesmentioning
confidence: 99%